TOXIC METALS BIOACCUMULATION IN DIFFERENT ORGANS OF FISH HARVESTED FROM ZOBE DAM, KATSINA STATE, NIGERIA USING RELATIVE INSTRUMENTAL NEUTRON ACTIVATION ANALYSIS - Bichi, A. H.; Joseph, Emmanuel; Abubakar, I. (FUDMA Journal of Sciences, 2025)
Instrumental neutron activation (INAA) technique has been applied to investigate the concentrations of possibly toxic elements in organs of Oreochromis niloticus and Clarias gariepinus from Zobe Dam, Katsina State. Consumption of fish offers unique nutritional and health benefits and is considered a key element in a healthy diet. However, despite its nutritional value, fish living in a polluted environment can accumulate the toxic metals at high concentration causing serious risk to human health when consumed. The main goal of this study is to investigate the possible toxic elements concentrations as well as assess the possible health implications they may pose to human via the fish consumption. Six (6) possibly toxic elements As, Br, Co, Cr, V, and Ba were detected by the INAA techniques. The dietary intake of some of the possibly toxic elements was estimated for tissue by considering WHO/FAO tolerable daily intake of adults (TDI/70 kg). Other organs were neglected according to the consumption pattern of the population in the study area. Our result of the estimated dietary intake showed that, the concentration of the detected toxic elements in tissue of both fish species were considerably below the estimated daily tolerable human consumption limits set by the WHO/FAO except for Cobalt which shows concentration higher than the recommended daily intake limit. Therefore, consumption of tissue of the studied fish species harvested from Zobe Dam is considered safe.
Keywords: Bioaccumulation; Concentration; Consumption; INAA; Zobe Dam